Five Types of Personality and the locus of Internal Control in relation to Preeclampsia Pregnancy - Lusiana Meinawati (Institute of Medico-Legal Publications, 2018)
Preeclampsia is one of the highest mortality factors for pregnant women. Hypertension, one of the main characteristics of preeclampsia, is the second main causes of maternal mortality at 27.1%. During pregnancy, they will face physical and psychological stressors. One of the factors related to stress management is the woman’s characteristics and the locus of control. This study aims to identify the relationship between the five types of personality and the locus of internal control in relation to preeclampsia in pregnancy. This study used a cross-sectional design. The population of this study consisted of pregnant women with preeclampsia who came to the independent midwifery practices in Jombang; 135 women total. The sample was selected using the total sampling method. The data was analysed by regression analysis. The independent variables related to preeclampsia included neuroticism (p=0.003; Exp(B)=11.234) and the negative internal locus of control (p=0.000; Exp(B)=11.387). It is expected that midwifery professionals can provide counselling services effectively and efficiently in relation to performing antenatal care services.